A comparative study of twenty-five micrograms oral versus vaginal misoprostol for labour induction at term - Sudheera, Yandapalli; Mubeena, Shaik; Myneedi, Vineela (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Many societies from primitive to the modern, have been interested in, the ability to induce labour. The majority of women’s labours begins spontaneously and end in a normal vaginal delivery at or near term. Labour induction is often required due to medical or obstetric complications during pregnancy. This procedure has the potential to provide significant maternal and perinatal advantages. Methods: Cases for this study were collected from the Narayana Medical College and Hospital Nellore between January 2021 and December 2022. Informed consent was obtained from 100 pregnant women with indications for induction of labour in the third trimester, who were divided into two groups of 50 each for the oral and vaginal routes. The study was conducted after taking approval from institute ethics committee. Results: A total of 100 individuals were included in the trial, with each group of 50 receiving either oral or vaginal misoprostol 25mcg, 4th hr upto a maximum of 6 doses. In the vaginal misoprostol and oral misoprostol group, Primigravida required more doses of oxytocin compared to multigravida. Conclusions: Vaginal misoprostol had lesser induction-delivery interval, lesser c-section rates than oral misoprostol. Therefore, misoprostol when administered vaginally has higher efficacy than oral route. The increased efficacy of misoprostol raises the possibility of a local cervical effect, when administered vaginally.